Motivation for Implementing Halal Standards of Food and Beverage MSMEs in DKI Jakarta - Retno Titisari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The MSME industrial sector is a vital economic driver and the primary pillar of Indonesia's economic structure. In 2019, Indonesia's GDP totaled IDR 15.83 trillion, with MSMEs accounting for IDR 9.48 trillion. Halal certification for MSMEs has become a strategic priority for the government as it seeks to strengthen the MSME industry and increase global competitiveness. Despite the fact that this halal certification is being regarded as a critical instrument for MSMEs' comeback, the bulk of them still lack it. As a result, this study focuses on the variables that encourage MSMEs (reputation enhancement, religiosity, process improvement, product quality improvement, and market share) to accelerate the adoption of halal standards among halal food and beverage producers in DKI Jakarta. To do this, the researchers used a quantitative research methodology. Primary data were acquired by surveys and processed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that all five criteria have a considerable beneficial impact on driving MSMEs to apply halal standards, with market share being the most effective factor. Finally, internal motivation is crucial to the adoption of halal standards among halal food and beverage MSMEs in DKI Jakarta.